2020
DOI: 10.3389/fimmu.2020.01290
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Regulation of Gene Expression Networks by Surfactant Protein A (SP-A) Variants in Alveolar Macrophages in Response to Klebsiella pneumoniae

Abstract: Surfactant protein A (SP-A) in addition to its surfactant-related functions interacts with alveolar macrophages (AM), the guardian cells of innate immunity in the lungs, and regulates many of its functions under basal condition and in response to various pressures, such as infection and oxidative stress. The human SPA locus consists of two functional genes, SFTPA1 and SFTPA2, and one pseudogene. The functional genes encode human SP-A1 and SP-A2 proteins, respectively, and each has been identified with several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 129 publications
(258 reference statements)
2
35
0
Order By: Relevance
“…Thus, the present results are consistent with a possible protective role of SP-A2 by modulating the NAD(H) redox status and the oxidative stress after ozone exposure. In fact, it has been previously postulated that SP-A has an antioxidant role in the lung by scavenging ROS [ 73 ] or possibly regulating NADPH oxidase activity in human monocyte derived macrophages [ 74 ] which may or may not capture the in vivo effect of the ozone-induced oxidative stress in the lungs. It has been shown that the tissue-specific alveolar macrophages differ from monocyte-derived macrophages in response to injury [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present results are consistent with a possible protective role of SP-A2 by modulating the NAD(H) redox status and the oxidative stress after ozone exposure. In fact, it has been previously postulated that SP-A has an antioxidant role in the lung by scavenging ROS [ 73 ] or possibly regulating NADPH oxidase activity in human monocyte derived macrophages [ 74 ] which may or may not capture the in vivo effect of the ozone-induced oxidative stress in the lungs. It has been shown that the tissue-specific alveolar macrophages differ from monocyte-derived macrophages in response to injury [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection for the young mice was performed as described previously [ 24 ] and for the aged mice as described previously [ 24 ], except a significantly higher CFU (~1800) inoculum was used for the aged mice. The higher dose was needed, because unlike the younger mice, all of the aged mice recovered if they were infected with the low CFU (~450) inoculum used for the young mice [ 39 , 40 , 60 ]. Briefly, hTG mice, SP-A1 (6A 2 , 6A 4 ), SP-A2 (1A 0 , 1A 3 ), and SP-A-KO male and female mice were anesthetized with a mixture of ketamine (Vedco.…”
Section: Methodsmentioning
confidence: 99%
“…Inc, St. Joseph, MO, USA) and xylazine (Akorn. Inc, lake forest, IL, USA) and infected with K. pneumoniae (~1800 CFU/mouse) in 50 µL of PBS delivered to oropharynx and aspirated after a brief nasal occlusion [ 60 , 81 ]. The mice were monitored for survival twice a day (morning and evening, 6–8 h difference between the two daily observations and at each observation time point, each mouse was observed for 5–10 min) for 14 days after infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations